Four new species of Thubdora Park, 2018 and one new species of Torodora Meyrick, 1894 (Lepidoptera, Lecithoceridae, Torodorinae) from Tanzania - Park, Kyu-Tek; Cho, Soowon (Zootaxa, 2021)
Four new species of Thubdora Park, 2018 and one new species of Torodora Meyrick,1894 are described from Tanzania. The new species are Thubdora forficatalis Park & Cho, sp. nov., T. mufindiensis Park & Cho, sp. nov., T. ochrospilosa Park & Cho, sp. nov., T. tanzaniana Park & Cho, sp. nov., and Torodora melanonota Park & Cho, sp. nov. Images of adults and genitalia of the new species are provided and a map for the type localities of the new species is given.